Diagnostic accuracy of18F-FDG PET/CT in the evaluation of recurrent ovarian cancer - Nawi, Norazlina Mat; Mohamad, Irfan; Khader, Mohamed Ali Abdul; Shuaib, Ibrahim Lutfi (Bangladesh Journal of Medical Science, 2021)
Objective: Ovarian cancer recurrence is often a major problem for patients who have undergone treatment. This prospective study was undertaken to evaluate the diagnostic accuracy of positron emission tomography (PET) with F-18 fluorodeoxyglucose (FDG)/ computed tomography (CT) in patients with suspected for ovarian cancer recurrence. Methods: A total of 43 women who underwent surgery or chemotherapy for ovarian cancer were enrolled in this study. They underwent18 F-FDG PET/CT scan due to raised CA-125 levels, clinical suspicion of ovarian cancer recurrence, or alterations detected on CT.18 F-FDG PET/CT findings for the women were compared with the final diagnosis. Results: CA-125 was elevated in 13 patients, while 34 patients presented with alterations on CT, and 9 patients presented with both results’ positivity. 17 patients confirmed to have an ovarian cancer recurrence, all with abnormal findings on PET/ CT. 20 patients remained disease-free during follow-up, all with normal PET/CT findings. There were 9 patients with raised CA-125 levels and normal conventional imaging, all with positive18 F-FDG PET/CT. Among the 30 patients with normal CA-125 levels, 9 patients presented with a positive PET/CT scan. Lymph nodes were the most frequent site. Its sensitivity, specificity, positive predictive value, and negative predictive valuewere 94%, 91%, 77%, and 95%, respectively. Conclusion: 18F-FDG PET/CT is a useful modality for evaluating the cancer recurrence and extent of the disease. Lymph nodes were the most frequent site. However, there was no statistical significance found between CA-125 levels and 18F-FDG PET/CT findings. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.302-312